Adoption Behaviour of Pigeonpea Growers in Allahabad District of Uttar Pradesh - Srivsatava, J.P.; Bose, Dipak Kumar; Singh , Jitendra (Indian Journal of Extension Education, 2013)
Pigeonpea is most important pulse crop enterprise in U.P. Efforts are being made by extension functionaries to boost-up  the production and productivity of the pigeon pea, even though, there exists the gap between the yield obtained at research  farm and farmers' field, it might be due to adoption gap. Keeping this in view an investigation was carried out in  Karchhana block of Allahabad district during 2011-12 in order to determine the level of adoption of improved practices of  pigeon pea production technology. The study inferred that majority of the respondents had medium level of adoption  followed by high and low level of adoption. The variables like age, education, extension contact and mass media exposure  were found to be positively and significantly corelated with the adoption behavior of the pigeon growers. There is a  considerable scope for enhancing the production of the pigeon pea subject to the need based training imparted to the  growers so that they could reap the benefits by adopting the improved package of practices.
Keywords: Adoption behaviour; pigeon pea growers; improved practices